A combined AHP and TOPSIS approach for prioritizing the attributes for successful implementation of agile manufacturing. Issue 7 (20th February 2020) - Kumar, Rahul; Singh, Kanwarpreet; Jain, Sanjiv Kumar
Abstract : Purpose: The concept of agile manufacturing is becoming critically important to manufacturing industry due to rapid industrialization, fluctuating customer demand, and turbulent business environment. The aim of this study is to prioritize the attributes for successful implementation of agile manufacturing using a combined analytical hierarchy process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) approach in Indian manufacturing industry. Design/methodology/approach: The current study identifies eight agile manufacturing attributes through literature review and discussion with subject experts. The experts from different manufacturing industry have been asked to provide data for pairwise comparison of attributes. Afterward, an integrated AHP and TOPSIS approach is employed. The AHP is used to drive the priority weights of the attributes, and TOPSIS is used for prioritizing the attributes for successful implementation of agile manufacturing. Findings: "Information technology, " "human resource management-related issues, " "customer-related issues, " "leadership support, " and "organizationalc related-issues" have been ranked as the top five significant and contributing attributes, which can pave the path for top management to concentrate on the critical areas and allocate significant resources to ensure successful implementation of agile manufacturing. Originality/value: This research integrates AHP and TOPSIS to prioritize the attributes for successful implementation of agile manufacturing, which are further validated by comparing the ranks obtained through respective approach and sensitivity analysis.